2017
DOI: 10.1155/2017/9651371
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Modulates Insulin Signaling in a Rat Model of Nonalcoholic Steatohepatitis

Abstract: A growing body of evidence has shown the beneficial effects of salidroside in cardiovascular and metabolic diseases. This study aimed to evaluate the therapeutic effects of salidroside on nonalcoholic steatohepatitis (NASH) in rats and explore the underlying mechanisms related to insulin signaling. A rat model of NASH was developed by high-fat diet for 14 weeks. From week 9 onward, the treatment group received oral salidroside (4.33 mg/kg) daily for 6 weeks. Salidroside effectively attenuated steatosis and vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We found that salidroside-stimulated AMPK activation could reduce lipid accumulation in muscle and liver tissues of db/db mice, suggesting that salidroside may be used for the treatment of NAFLD [ 25 ]. Yang et al [ 36 ] and Li et al [ 44 ] reported that salidroside could prevent liver injury in the rat or mice NASH model induced by HFD feeding, and these findings raised that the antioxidant and hepatic insulin signaling regulation are involved in the action of salidroside, respectively. However, whether or not salidroside is suitable for NAFLD, treatment and mechanisms underlying its effects have not been fully elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…We found that salidroside-stimulated AMPK activation could reduce lipid accumulation in muscle and liver tissues of db/db mice, suggesting that salidroside may be used for the treatment of NAFLD [ 25 ]. Yang et al [ 36 ] and Li et al [ 44 ] reported that salidroside could prevent liver injury in the rat or mice NASH model induced by HFD feeding, and these findings raised that the antioxidant and hepatic insulin signaling regulation are involved in the action of salidroside, respectively. However, whether or not salidroside is suitable for NAFLD, treatment and mechanisms underlying its effects have not been fully elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…HE staining was performed on 4-μm-thick sections according to the standard published protocols [23]. Sections were examined by experienced liver pathologists.…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…Thus, they have the potential to hinder the progression of NASH to HCC. Salidroside (31) reduced hepatic lipid accumulation, the inflammatory response and insulin resistance in NAFLD rats ( Li et al, 2017 ). In an HFD-induced NASH model in mice, salidroside (31) treatment significantly improved HFD-induced intestinal bacterial and bile acid disturbances, thus demonstrating the potential role of salidroside (31) in NASH treatment via the intestinal microbial-bile acid-FXR axis ( Li H. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%